The Effect of Flaxseed Oil (Linum usitatissimum) on Lipid Metabolism of Cholesterol Fed Rats. - Al-Hadrawy, Suaad M J; Al-Hilaly, Ikhlass A; Al-Kafajy, Haider A Thanwan (Al-Nahrain Journal of Science, 2018)
This research designed to study the effects of flaxseed oil (0.25 ml) orally given for 28 days on the total cholesterol concentration and on lipid lipoprotein in the blood of cholesterol fed rats. Methods: Randomly 12 adult female rats were divided into 4 groups (3 animals for each group). The control group ( group I) were fed with standard pellet diet, the second group (group II) were fed with 1% cholesterol diet, the third group (group III) were daily administered (0.25 ml) of the flaxseed oil along with high cholesterol diet, and the fourth group (group IV) received daily (0.25 ml) of flaxseed oil. Results: The results showed a disturbance state in blood lipids in the animals that fed with diet contain cholesterol characterized with significant increase in total cholesterol (TC) and the concentration of low density lipoprotein (LDL-C) and triglyceride (TG) and in the very low density lipoprotein (VLDL-C) in the serum and a significant decrease in the level of high density lipoprotein (HDL-C) concentration. Also the result showed that flaxseed oil administration has no protective effects against this lipid disturbance which induced by cholesterol use. Conclusion: The treatment with flaxseed oil didn’t cause significant decrease in total cholesterol level and didn’t cause increase the level of High density lipoprotein in the plasma of treated rats.